Optimizing Teaching Styles in Playgroups at Inclusive Schools: Adaptation, Creativity, and Inclusivity at Talenta Kudus Inclusive Classroom - Afrianingsih, Anita; Tarjiat, Ita Tara; Mufid, Mufid (THUFULA, 2025)
Teaching in inclusive schools faces significant challenges, especially due to the diversity of students' learning needs. Children with special needs (ABK) require different teaching strategies than children without special needs, and in the context of playgroups, these differences are even more complex. Inclusive schools aim to unite children with special needs with children in general in the same learning environment. This requires the application of adaptive, creative, and inclusive teaching styles from playgroup teachers. This study aims to explore the application of effective teaching styles at KB Inklusi Talenta Kudus, with a focus on method adaptation, the use of creativity in teaching, and the application of inclusive principles. The data for this study were obtained through observation, interviews with teachers, and relevant literature studies. The results of the study indicate that a combination of individual adaptation, creativity in classroom management, and commitment to inclusive values play an important role in supporting the success of the teaching and learning process in inclusive schools.